PENGARUH PAKET EDUKASI HBsAg TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL TRISEMESTER 1 TENTANG HBsAg DI WILAYAH KERJA PUSKESMAS TAMANAN KABUPATEN BONDOWOSO - Nailah Islahiyah (JURNAL KESEHATAN INDRA HUSADA, 2019)
Background: The incidence of hepatitis B virus infection in pregnant women is of particular concern, because in addition to causing health problems in the mother, it can also transmit to the baby she is carrying, especially during the birth process. Purpose: The purpose of this study is to determine the effect of HBsAg education packages on the knowledge and attitudes of 1st trimester pregnant women about HBsAg. Methodology: This study used a pre-experimental research design with the One Group Pretest-Posttest approach, using a questionnaire, the sample of the study was 35 respondents using total sampling technique. Conclusion: From this study the results obtained are that there is a significant influence with the value of P = 0.000. This means that there is an influence of the HBsAg education package on the knowledge and attitudes of 1st trimester pregnant women about HBsAg in the work area of the Tamanan Health Center in Bondowoso District. Keywords: Educational Package,Knowledge,HbsAg,Attitude,Pregnant Women